Helminthic host defense peptides: using the parasite to defend the host - Mladineo, Ivona; Rončević, Tomislav; Gerdol, Marco; Tossi, Alessandro (Trends in parasitology, 2023)
Parasitic helminths are destined to share niches with a variety of microbiota that inevitably influence their interaction with the host. To modulate the microbiome for their benefit and defend against pathogenic isolates, helminths have developed host defense peptides (HDPs) and proteins as integral elements of their immunity. These often exert a relatively nonspecific membranolytic activity toward bacteria, sometimes with limited or no toxicity toward host cells. With a few exceptions, such as nematode cecropin-like peptides and antibacterial factors (ABFs), helminthic HDPs are largely underexplored. This review scrutinizes current knowledge on the repertoire of such peptides in helminths and promotes their research as potential leads for an anti-infective solution to the burgeoning problem of antibiotic resistance.
Keywords: microbiome; antimicrobial peptides; host defense peptides; helminths; Bacteria; Helminths; Animals; paraziti; Parasites; immunity; cizopasní červi; zvířata; Antimicrobial Cationic Peptides; kationické antimikrobiální peptidy